Welfare and the Constitution - Barber, Sotirios A. (New forum books., 2003)
Welfare and the Constitution defends a largely forgotten understanding of the U.S. Constitution: the positive or "welfarist" view of Abraham Lincoln and the Federalist Papers. Sotirios Barber challenges conventional scholarship by arguing that the government has a constitutional duty to pursue the well-being of all the people. He shows that James Madison was right in saying that the "real welfare" of the people must be the "supreme object" of constitutional government. With conceptual rigor set in fluid prose, Barber opposes the shared view of America's Right and Left: that the federal constit